Updates on the controversial roles of regulatory lymphoid cells in idiopathic pulmonary fibrosis - Curioni, Anna V.; Borie, Raphaël; Crestani, Bruno; Helou, Doumet Georges (Frontiers in Immunology, 2024)
Idiopathic pulmonary fibrosis (IPF) is the most common and severe form of pulmonary fibrosis, characterized by scar formation in the lung interstitium. Transforming growth factor beta (TGF-β) is known as a key mediator in the fibrotic process, acting on fibroblasts and mediating their proliferation and differentiation into myofibroblasts. Although the immune system is not considered responsible for the initiation of IPF, markers of tolerogenic immunity define the profibrotic microenvironment in the lungs. In homeostatic conditions, regulatory T cells (Tregs) constitute the main lymphoid population responsible for maintaining peripheral tolerance. Similar to Tregs, regulatory B cells (Bregs) represent a recently described subset of B lymphocytes with immunosuppressive functions. In the context of IPF, numerous studies have suggested a role for Tregs in enhancing fibrosis, mainly via the secretion of TGF-β. In humans, most studies show increased percentages of Tregs associated with the severity of IPF, although their exact role remains unclear. In mice, the most commonly used model involves triggering acute lung inflammation with bleomycin, leading to a subsequent fibrotic process. Consequently, data are still conflicting, as Tregs may play a protective role during the inflammatory phase and a deleterious role during the fibrotic phase. Bregs have been less studied in the context of IPF, but their role appears to be protective in experimental models of lung fibrosis. This review presents the latest updates on studies exploring the implication of regulatory lymphoid cells in IPF and compares the different approaches to better understand the origins of conflicting findings.